2001
DOI: 10.1088/0960-1317/11/4/318
|View full text |Cite
|
Sign up to set email alerts
|

Powder-blasting technology as an alternative tool for microfabrication of capillary electrophoresis chips with integrated conductivity sensors

Abstract: The fabrication and characterization of a microfluidic device for capillary electrophoresis applications is presented. The device consists of a glass chip which contains a single separation channel as well as an integrated conductivity detection cell. In contrast to most microfluidic glass devices the channels are not wet etched in HF but machined by the newly developed micro powder-blasting technique which allows the creation of microstructures below 100 µm, and additionally makes parallel hole machining at v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
98
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 9 publications
(9 reference statements)
1
98
0
Order By: Relevance
“…The used photoresist was stripped from the wafer in acetone. Through-holes and deep channels like the gas channel with a depth of 100 m were made using powder blasting [25]. A photosensitive protective foil, Ordyl BF410, was laminated onto the wafer and structured using photolithography and developed in sodium carbonate.…”
Section: A Miniaturized Detection Systemmentioning
confidence: 99%
“…The used photoresist was stripped from the wafer in acetone. Through-holes and deep channels like the gas channel with a depth of 100 m were made using powder blasting [25]. A photosensitive protective foil, Ordyl BF410, was laminated onto the wafer and structured using photolithography and developed in sodium carbonate.…”
Section: A Miniaturized Detection Systemmentioning
confidence: 99%
“…With such abrasive techniques, one can achieve high erosion rates; higher than those that can be obtained with conventional dry or wet etching processes such as plasma etching and chemical etching. In the field of microelectromechanical systems (MEMS), powder blasting has already been used for the fabrication of inertial sensors [2], peristaltic micropumps [3] and miniaturized capillary electrophoresis chips [4]. Erosion with sharp particles is also a widely used technique in aerospace and automotive industries.…”
Section: Introductionmentioning
confidence: 99%
“…Powder blasting has been evaluated for structuring microfluidic chips for electrophoresis [9][10][11][12]. It could be shown that such devices can in principal be applied in chip electrophoresis.…”
Section: Introductionmentioning
confidence: 99%